HISTORY AND PSYCHOLOGY OF ADVERTISING IN THE INSTITUTIONAL DEVELOPMENT OF ORGANIC AGRIBUSINESS - Bilotkach, Ihor (Current Problems of Sustainable Development, 2026)
The article examines the role of the historical evolution of advertising and psychological mechanisms of advertising influence in shaping the behavior of organic product consumers and the institutional development of organic agribusiness. It is substantiated that since the early twentieth century, when W. Dill Scott published “The Theory of Advertising,” psychological approaches to advertising gradually transformed from the theory of influence and persuasion to modern models that take into account emotions, values, and social norms of consumers. The key psychological mechanisms of advertising impact on consumers of organic products are identified: emotional communication, signaling about quality and reliability, building trust, appeals to environmental values and calls for positive change. It has been established that modern advertising of organic goods effectively uses the concept of “warm glow” (satisfaction from environmental care) and self-expressive benefits, which stimulate purchases and emerge as key motivators of consumer behavior. It is shown that the institutional development of organic agribusiness is impossible without building public trust and support, which advertising and marketing communications achieve through psychologically substantiated approaches. Formal institutions (laws, standards, certification) and informal ones (public opinion, cultural norms, environmental consciousness) interact through advertising communications that actualize values and motivate consumers to support the organic sector. It is concluded that understanding the historical development of advertising psychology and modern psychological models of consumer behavior allows organic agribusinesses to develop more effective marketing strategies, build stable brand trust, increase competitiveness in national and world markets, and promote the institutional development of the organic sector in Ukraine.
Keywords: advertising; advertising psychology; organic agribusiness; institutional development; consumer behavior; psychological mechanisms of influence; environmental values; marketing communications